PERANAN DINAS KEBERSIHAN DAN PERTAMANAN DALAM MENINGKATKAN KEBERSIHAN LINGKUNGAN DI KOTA SAMARINDA - Iswanto .; Djumadi .; Achmad Djumlani (Jurnal Administrative Reform, 2017)
The purpose of this study is to describe and analyze the role of the Department of Hygiene and in improving environmental hygiene.  The results showed Role Department of Hygiene and Samarinda in improving environmental hygiene in Samarinda less than optimal. Indicated by the level of achievement of the set parameters, namely of 6 parameters of which there are two indicators such as its role as waste management and supervision less effective nonetheless cumulatively role and Sanitation Department  can be implemented quite effectively.